2015
DOI: 10.1111/oik.02718
|View full text |Cite
|
Sign up to set email alerts
|

The highs and lows of dispersal: how connectivity and initial population size jointly shape establishment dynamics in discrete landscapes

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…Presence of positive density-dependent dispersal analysis Using Approximate Bayesian Computation (ABC), we checked for the presence of positive density-dependent dispersal for Trichogramma chilonis in our experimental design by comparing two different scenarios, one with fixed dispersal and one with positive density-dependent dispersal (with a dependence of the form (7)). This analysis confirmed that the positive density-dependent dispersal scenario is the most likely, as suggested by a previous study with a comparable protocol (Morel-Journel et al, 2016). More details on the ABC analysis are presented as Supplementary Information S2.…”
Section: Experimental Study: Propagation Of a Parasitoid Wasp In A MIsupporting
confidence: 87%
“…Presence of positive density-dependent dispersal analysis Using Approximate Bayesian Computation (ABC), we checked for the presence of positive density-dependent dispersal for Trichogramma chilonis in our experimental design by comparing two different scenarios, one with fixed dispersal and one with positive density-dependent dispersal (with a dependence of the form (7)). This analysis confirmed that the positive density-dependent dispersal scenario is the most likely, as suggested by a previous study with a comparable protocol (Morel-Journel et al, 2016). More details on the ABC analysis are presented as Supplementary Information S2.…”
Section: Experimental Study: Propagation Of a Parasitoid Wasp In A MIsupporting
confidence: 87%
“…While individuals were able to move freely between patches by walking through pipes, the dispersal rates in this experimental system remained low. Previous experiments (Morel-Journel et al 2016) in similar conditions showed that most individuals remained in their natal patch, and no individual was ever found further that one patch away from its natal patch.…”
Section: Methodsmentioning
confidence: 83%
“…Dispersal mortality risks and Allee effects were considered separately during the simulations, and previous results by Morel-Journel et al (2016) concluded that T. chilonis suffered from no demographic Allee effect in this particular experimental setting. However, the two mechanisms can also influence each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations